Pengawasan sistem sop (standard operating procedure) baru oleh supervisor pada front office department sativa sanur cottages - Murni, Ni Nengah; Jamin Ariana, I Nyoman; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas, 2019)
The tourism industry, especially accommodation such as hotels and others, must have productive, quality, and professional in serving guests. Therefore a Supervisor must be able to educate and guide his staff according to their standards and abilities to create productive human resources by providing supervision or supervising them. This study aims to determine the supervision of new SOP system carried out by the Supervisor and the perception of the Front Office Staff to the Supervisor in carrying out supervision in the Front Office Department of Sativa Sanur Cottages. This research in collecting data used observation, interviews and documentation. The data analysis technique is descriptive qualitative and supported by the attitude scale method or Likert scale to determine the perception of the Front Office Staff. The results of this study indicate that supervision for new SOP sistem is carried out using four stages of supervision that are carried out every day, every month every six months, and the results obtained from the monitoring show that the performance of Front Office staff of Sativa Sanur Cottages is good in accordance with predetermined standards. For the perception of the Front Office Staff towards Supervisor Nyoman Nurpatria Krisna in conducting supervision, the overall score was obtained with an average of 3.81, namely the criteria of "good", and also statement from the Front Office Manager that is was good, so Nyoman Nurpatria Krisna as the Front Office Supervisor at Sativa Sanur Cottages had performed her duties and responsibilities accordingly with predetermined standards. The suggestions submitted to Sativa Sanur Cottages, especially for Front Office Supervisors, are able to maintain the manner of supervision that is done now and even improve it to be better in the future in order to create qualified employees and productivity in doing work. Keywords: Supervision, SOP, Perception, and Sativa Sanur Cottages.